A Conductive Polypyrrole‐Coated, Sulfur–Carbon Nanotube Composite for Use in Lithium–Sulfur Batteries. Issue 4 (27th February 2013) - Wang, Jiazhao; Lu, Lin; Shi, Dongqi; Tandiono, Richard; Wang, Zhaoxiang; Konstantinov, Konstantin; Liu, Huakun
Abstract A novel ternary composite, polypyrrole (PPy)‐coated sulphur–carbon nanotube (S‐CNT), is synthesised by using an in situ, one‐pot method. Firstly, elemental sulfur is loaded into the CNT network by a solution‐based processing technique. Then conducting PPy is coated on the surface of the S‐CNT composite to form the S‐CNT‐PPy ternary composite by carrying out polymerization of the pyrrole monomer in situ. The ternary composite is tested as a cathode for lithium–sulfur batteries. The results show that PPy coating improves significantly the performance of the binary composites (S‐CNT and S‐PPy). The conducting PPy is believed to serve multiple functions in the composite: as a conducting additive, an active material, and an adsorbent and container to confine the polysulfides and prevent them from dissolving into the electrolyte. As a result, PPy coating on the S‐CNT composite enhances its conductivity, capacity and cycling stability. The capacity of S‐CNT‐PPy is about 600 mAh g−1 after 40 cycles, which is much higher than for the S‐CNT composite (430 mAh g−1)